Fostering Social Resilience in Indigenous Communities: Maqāṣid al-Sharī‘ah as a Framework for Kaili Da'a Empowerment - Suhri Hanafi; Mohamad Oktafian; Sitti Nurkaerah; Ahmad Syafi'i (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2026)
The low level of education among the Kaili Da’a community impacts the vulnerability of family resilience, particularly in economic and social aspects, as reflected in the dominance of livelihoods in the informal sector, where 50.3% of Kaili Da’a livelihoods are in agriculture and gardening, while the remainder work as traders, miners, or vendors in markets. This study aims to analyze the strengthening of family resilience among the Kaili Da’a indigenous community from the perspective of Jamaluddin Athiyyah’s Maqāṣid al-Sharīʻah using qualitative methods as well as Miles and Huberman’s analysis. The results indicate that family resilience among the Kaili Da’a community encompasses five dimensions: legal and structural quality, physical resilience, economic resilience, socio-psychological resilience, and socio-cultural resilience. However, comprehensive fulfillment of indicators is only observed in the dimensions of legal and structural quality, physical resilience, and socio-cultural resilience, while the economic and socio-psychological dimensions remain suboptimal. From the perspective of Maqāṣid al-Sharīʻah, these findings indicate that the family resilience of the Kaili Da’a community reflects the dimensions of the individual, family, society, and humanity. This study contributes to the development of an analysis of family resilience based on Jamaluddin Athiyyah’s Maqāṣid al-Sharīʻah, which integrates the local values of the Kaili Da’a indigenous community with an Islamic perspective. This study also enriches the theoretical discourse on family resilience grounded in local culture and Maqāṣid al-Sharīʻah.